Bicyclic 6 + 6 systems: the chemistry of pyrimido[4, 5-d]pyrimidines and pyrimido[5, 4-d]pyrimidines. Issue 53 (30th September 2019) - Monier, M.; Abdel-Latif, Doaa; El-Mekabaty, Ahmed; Elattar, Khaled M.
Abstract : The present investigation provides an overview of the chemistry of pyrimido[4, 5- d ]pyrimidines and pyrimido[5, 4- d ]pyrimidines. The synthetic methods, reactivities, and biological applications are described. Abstract : The present study provides an overview of the chemistry and biological significance of pyrimido[4, 5- d ]pyrimidine and pyrimido[5, 4- d ]pyrimidine analogs as types of bicyclic [6 + 6] systems. The main sections include: (1) synthesis methods; (2) the reactivities of the substituents linked to the ring carbon and nitrogen atoms; and (3) biological applications. A discussion demonstrating the proposed mechanisms of unexpected synthetic routes is intended. The aim of this study is to discuss the synthetic significance of the titled compounds and to establish the biological characteristics of this class of compounds as studied to date, where the compounds have been applied on a large scale in the medical and pharmaceutical fields. This survey will help researchers in the fields of synthetic organic and medicinal chemistry to undertake and improve new approaches for the construction of new standard biological components.